2015
DOI: 10.1016/j.scr.2015.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of survival factor for primitive chronic myeloid leukemia cells using induced pluripotent stem cells

Abstract: A definitive cure for chronic myeloid leukemia (CML) requires identifying novel therapeutic targets to eradicate leukemia stem cells (LSCs). However, the rarity of LSCs within the primitive hematopoietic cell compartment remains a major limiting factor for their study in humans. Here we show that primitive hematopoietic cells with typical LSC features, including adhesion defect, increased long-term survival and proliferation, and innate resistance to tyrosine kinase inhibitor (TKI) imatinib, can be generated d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 71 publications
(115 reference statements)
1
33
0
Order By: Relevance
“…The mutation or deletion of C/EBPα may result in arrest of the transit of common myeloid progenitors into granulocyte-monocyte progenitors, and lead to a reduction in granulocytes and monocytes (22). In addition, deficiency of C/EBPα in mice may induce disorder in myeloproliferation (19). In the present study, significantly lower expression of C/EBPα was detected in patients with CML, compared with that in normal controls.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…The mutation or deletion of C/EBPα may result in arrest of the transit of common myeloid progenitors into granulocyte-monocyte progenitors, and lead to a reduction in granulocytes and monocytes (22). In addition, deficiency of C/EBPα in mice may induce disorder in myeloproliferation (19). In the present study, significantly lower expression of C/EBPα was detected in patients with CML, compared with that in normal controls.…”
Section: Discussionsupporting
confidence: 43%
“…CML is a myeloproliferative disorder originating from hematopoietic stem cells with constitutive expression of the BCR/ABL oncoprotein (19). Imatinib was the first target drug approved by the US Food and Drug administration for the treatment of CML, and remains a commonly used drug in clinical therapy (20).…”
Section: Discussionmentioning
confidence: 99%
“…Our studies have revealed that hematopoietic progenitors within the CD34 + cell population in human PSC cultures could be precisely identified based on the expression of leukosialin (CD43), that reliably separates them from CD43 − CD31 + endothelial cells and CD43 − CD31 − cells with mesenchymal characteristics . CD34 + CD43 + PSC‐derived progenitors are composed of two major populations: (a) erythromegakaryocytic progenitors that coexpress CD235a and CD41a, and (b) CD235a − CD41a − CD43 + CD45 +/− multilineage progenitors that are lacking lineage markers and display CD90 + CD117(c‐kit) + CD38 − CD45RA − phenotype typical for human HSCs emerging in AGM (Fig. ).…”
Section: Hematopoietic Differentiation and Engraftment Of Human Plurimentioning
confidence: 94%
“…). The PCS‐derived lin − CD34 + CD43 + CD45 +/− CD117 + CD90 + CD38 − CD45RA − population possesses CFC potential similar to cord blood lin − CD34 + CD38 − cells , LTC‐IC potential, a high ALDH activity, the ability to efflux rhodamine‐123, and is able to differentiate into all types of myeloid cells and lymphoid cells . Recent studies also demonstrated that hESC‐derived CD34 + CD38 −/low CD90 + CD45 + hematopoietic cells express GPI‐80, a marker of human fetal liver HSCs .…”
Section: Hematopoietic Differentiation and Engraftment Of Human Plurimentioning
confidence: 99%
See 1 more Smart Citation